3D Electron Microscopy Gives a Clue: Maize Zein Bodies Bud From Central Areas of ER Sheets - Arcalís, Elsa; Hörmann-Dietrich, Ulrike; Zeh, Lukas; Stoger, Eva (Frontiers in Plant Science, 2020)
Zeins are the main storage proteins in maize seed endosperm, and the onset of zein synthesis in young seeds challenges the endomembrane system and results in the formation of storage organelles. Even though zeins lack a conventional endoplasmic reticulum (ER) retention signal, they accumulate within the ER and assemble in conspicuous ER-derived protein bodies (PBs) stabilized by disulfide bridge formation and hydrophobic interaction between zein chains. Zein body formation during seed development has been extensively studied, as well as the mechanisms that lead to the initiation of PBs. However, the exact course of the PB formation process and the spatial relationship with the ER remain unclear. The development of serial block face scanning electron microscopy (SBF-SEM) techniques that allow three-dimensional imaging combined with the high resolution of electron microscopy provides new perspectives on the study of the plant endomembrane system. Here, we demonstrate that (i) the ER of maize seeds is mainly formed by massive sheets and (ii) PBs are not budding from tubules or the edge of sheets, but protrude from the entire surface of the ER sheet.